The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.ijfoodmicro.2008.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with aflatoxin contamination of peanuts from Western Kenya

Abstract: Aflatoxin contamination of peanuts poses a risk to human health and has been identified as a major constraint to trade in eastern Africa. A survey was carried out to obtain baseline data on levels of aflatoxin in peanuts from major production regions in western Kenya. A total of 384 and 385 samples from Busia and Homabay districts, respectively, were obtained and analyzed for aflatoxin content with an indirect competitive ELISA protocol. Levels of aflatoxin ranged from 0 to 2688 and 7525 microg/kg in samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
131
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(148 citation statements)
references
References 20 publications
15
131
0
2
Order By: Relevance
“…The range of aflatoxin contamination in groundnut samples in this study was comparable to those reported from local vendors, markets, and retail shops in Nigeria where aflatoxin‐B 1 detected in 64.2% of dry roasted groundnut (Bankole, Ogunsanwo, & Eseigbe, 2005). In Kenya, about 87.0% of groundnut were contaminated with <4 μg/kg of aflatoxin‐B 1 , while 7.5% exceeded national regulatory limited of 20 μg/kg (Mutegi et al., 2009). Similarly, 70% of groundnut samples from the DRC were found to contain higher than 5 μg/kg aflatoxins (Kamika & Takoy, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of aflatoxin contamination in groundnut samples in this study was comparable to those reported from local vendors, markets, and retail shops in Nigeria where aflatoxin‐B 1 detected in 64.2% of dry roasted groundnut (Bankole, Ogunsanwo, & Eseigbe, 2005). In Kenya, about 87.0% of groundnut were contaminated with <4 μg/kg of aflatoxin‐B 1 , while 7.5% exceeded national regulatory limited of 20 μg/kg (Mutegi et al., 2009). Similarly, 70% of groundnut samples from the DRC were found to contain higher than 5 μg/kg aflatoxins (Kamika & Takoy, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…2014; Mutegi, Ngugi, Hendriks, & Jones, 2009; Perrone et al., 2014; Williams et al., 2004). In animals, aflatoxins may lower resistance to diseases, interrupt vaccine‐induced immunity, and adversely affect growth and reproduction, causing serious economic losses (CAST 2003; Fink‐Gremmels, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…From the results, it can be concluded that because our country is in tropical area, the climate is suitable for fungal growth and peanuts are considered to be one of the most susceptible food materials for fungal growth and Aflatoxins productions. Several researchers have investigated peanuts for the presence of Aflatoxins, particularly AFB1 (Bankole et al, 2005;Barro et al, 2002;Mutegi et al, 2009). Iqbal et al (2013) reported the level of AFB1 ranging from 2.4 to 12.3 µg/kg but Wagacha et al (2013) reported AFB1 level in peanut products ranging from 0 to 1629 µg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Isolates were identified based on colony characteristics, strain morphology, macroscopic feature and microscopic feature [16]. The pure cultures were characterized and subsequently identified with the aid of a compound microscope as the representatives of the different colonies/fungi [16].…”
Section: Identification Of Fungimentioning
confidence: 99%
“…The pure cultures were characterized and subsequently identified with the aid of a compound microscope as the representatives of the different colonies/fungi [16].…”
Section: Identification Of Fungimentioning
confidence: 99%